Pharmacological Evaluation of Sambong Blumea balsamifera on Diuretic and Kidney Stone Dissolution Effects - Stefhene Jose; Maria Garcia; Juan Lopez; Ana Reyes; Luis Cruz (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study investigates the pharmacological effects of Blumea balsamifera (Sambong), a plant traditionally used in Filipino medicine for its diuretic and kidney stone-dissolving properties. Using Soxhlet and maceration extraction methods, Sambong extracts were obtained from the leaves and roots of the plant with ethanol as the solvent. Phytochemical analysis revealed bioactive compounds including flavonoids (luteolin, quercetin) and terpenoids (β-caryophyllene), known for their anti-inflammatory, antioxidant, and diuretic effects. The diuretic activity was tested in rats, where Sambong extracts (50 mg/mL and 100 mg/mL) were administered and the urine output was measured over 24 hours. The results showed a dose-dependent increase in urine output, with the 100 mg/mL dose producing a significant increase compared to the control group treated with furosemide. In addition to its diuretic effects, Sambong’s potential to dissolve kidney stones was evaluated by treating rats with calcium oxalate stones. The results indicated a significant reduction in stone size, with the 100 mg/mL dose achieving a 38% reduction. The comparative analysis with furosemide demonstrated that Sambong is a promising natural alternative for managing conditions such as hypertension, kidney stones, and urinary disorders, particularly in areas with limited access to pharmaceutical treatments. These findings validate Sambong’s traditional uses and highlight its therapeutic potential in modern healthcare. Future research should focus on clinical trials to assess its safety, optimal dosage, and efficacy in humans. Further investigation into its pharmacological mechanisms, including its anti-inflammatory and antimicrobial properties, could expand its use in treating various conditions, integrating Sambong into contemporary healthcare systems, especially in underserved areas.